2020
DOI: 10.1136/bmjsem-2020-000811
|View full text |Cite
|
Sign up to set email alerts
|

Trends in sports-related emergency department visits in the Netherlands, 2009–2018

Abstract: ObjectivesWe aim to describe time trends of severe sports-related emergency department (ED) visits in the Netherlands, from 2009 to 2018.MethodsData were extracted from the Dutch Injury Surveillance System by age, gender, sports activity and injury diagnosis, from 2009 to 2018. Absolute numbers and time trends of severe sports-related ED visits were calculated.ResultsBetween 2009 and 2018, the overall numbers of severe sports-related ED visits in the Netherlands have significantly decreased by 14% (95% CI −19%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…In general, the majority of respondents attending our sports injuries clinics are male young adults (18-29 years old), which is consistent with previous studies. 4,9,13,14 Similar to our earlier reports, it showed that soccer and basketball still remained as the main sports to incur the most sports-related injuries needing medical attention in the athletes. 9 In terms of the site of injuries, the knee and shoulder were the most prevalent among the three levels of athletes.…”
Section: Discussionsupporting
confidence: 83%
“…In general, the majority of respondents attending our sports injuries clinics are male young adults (18-29 years old), which is consistent with previous studies. 4,9,13,14 Similar to our earlier reports, it showed that soccer and basketball still remained as the main sports to incur the most sports-related injuries needing medical attention in the athletes. 9 In terms of the site of injuries, the knee and shoulder were the most prevalent among the three levels of athletes.…”
Section: Discussionsupporting
confidence: 83%